Forcing mechanisms of the 6 h tide in the mesosphere/lower thermosphere - C. Jacobi; C. Geißler; F. Lilienthal; A. Krug; A. Krug (Advances in Radio Science, 2018)
Solar tides such as the diurnal and semidiurnal tide, are forced in the lower and middle atmosphere through the diurnal cycle of solar radiation absorption. This is also the case with higher harmonics like the quarterdiurnal tide (QDT), but for these also non-linear interaction of tides such as the self-interaction of the semidiurnal tide, or the interaction of terdiurnal and diurnal tides, are discussed as possible forcing mechanism. To shed more light on the sources of the QDT, 12 years of meteor radar data at Collm (51.3° N, 13° E) have been analyzed with respect to the seasonal variability of the QDT at 82–97 km altitude, and bispectral analysis has been applied. The results indicate that non-linear interaction, in particular self-interaction of the semidiurnal tide probably plays an important role in winter, but to a lesser degree in summer. Numerical modelling of 6 h amplitudes qualitatively reproduces the gross seasonal structure of the observed 6 h wave at Collm. Model experiments with removed tidal forcing mechanisms lead to the conclusion that, although non-linear tidal interaction is one source of the QDT, the major forcing mechanism is direct solar forcing of the 6 h tidal components.